The effect of compound exercises in developing front and back stroke skills and some physiological indicators of badminton juniors - Al-Selmi, Abeer Dakhill Hatem (International Journal of Psychosocial Rehabilitation, 2020)
The accuracy of the skillful performance of the front and back dimensions of badminton in volleyball, occurs through the investment of complex exercises (physical skills) in a single performance and its characteristics that give the correct movement behavior and speed to the accuracy of the performance of the strokes as well as the identification of changes in some physiological indicators of By using these compound exercises. The research problem lies: I found a weakness in the accuracy of the performance of the front and back dimensions strike and diagnosed this through the tests that it conducted on the players to identify and know the problem, and attributed this weakness to a weakness in the necessary physical and skill abilities and this affects the accuracy of directing the performance of the front and back dimensions strike and some physiological variables. sought the researcher to prepare exercises characterized by combining physical performance and skill in the performance of one compound, this method is not found in the training of players badminton after reviewing their training goal of the new provision and the advancement of the process of training in badminton, it used the researcher of the curriculum pilot where the research community The two junior badminton players, whose number is ( 1 0 ) player, the researcher concluded Of : The exercise complex prepared by the researcher developed swung the machete dimensions of the front and rear and some physiological indicators of the plane badminton experimental group better than the control group sample.